Analisis Sistem Informasi Website Point Of Sale Menggunakan Metode System Development Life Cycle (SDLC) Prototype - Eko Andri Wibowo; Afgiyan Muslim; Fahri Husaini (PT Jurnal Cendekia Indonesia, 2025)
This study analyzes a website Point of Sale (POS) information system as a key solution to improve transaction efficiency and inventory management accuracy. We implemented the System Development Life Cycle (SDLC) Prototype Method, an approach that enables rapid and iterative development of a working system model. The goal was to validate and refine crucial features, such as the checkout process, CRUD product data, and pricing calculations, by engaging intensive user feedback from the outset. The system analysis results showed that the Prototype model successfully accelerated adaptation to functional requirements and maintained transaction data integrity. Validation of system functionality through Black Box Testing confirmed that all developed features worked accurately, proving that the SDLC Prototype is an effective framework for implementing a simple POS system.